High-performance work practices and service quality in mid-scale lodging industry - Mary Monica Jiony; Lew, Tek-Yew; Geoffrey Harvey Tanakinjal; Daria Gom; Ruth S. Siganul (Medwell Publishing, 2016)
The main objective of this research is to examine the important constructs of service quality in its relation to high performance work practice, with employee engagement as mediating factor. It attempts to identify the potential gap in the service quality performance of fulltime frontline employees in midscale lodging industry in Sabah, Malaysia. A preliminary study to complement a larger research, this study intends to use both qualitative and quantitative approach. The three-fold potential contributions of this paper include: enriching the literature of strategic Human Resource (HR) and Organizational Behavior (OB), as empirical evidence to the management of lodging industry and the service sector in general, and lastly, contributing toward the sustainable and robust performance of the ‘Sabah Hospitality Service Quality Performance.